Stakeholder Synergies for Enhancing Community-based Tourism Development - Gautam, Sahadev; Thapa, Asim (Journal of Tourism and Himalayan Adventures, 2023)
The rise of community-based tourism has ushered in a new era of home-staying. The paper intends to demonstrate a viable model of synergistic efforts of local community-led tourism, as well as to analyze its functions in culturally significant historic sites. The necessary data were collected in the touristic environment of the historical Panauti area. Open-ended questionnaires with homestay owners and people's representative respondents were employed for the study. This essay focuses on socio-historical perspectives, settings and conditions of modernization, and the success of homestays through collaborative function. The descriptive model was employed for the analysis. Collective features of homestay are recognized as fostering factors for intimate relationship among local people, and local government is also thought to produce sustainable resource use, social relationships, cooperation, and empowerment.